2021
DOI: 10.1007/s10943-021-01410-7
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Religious Coping Styles of Adolescents in Turkey During COVID-19

Abstract: We sought to evaluate the religious coping styles of adolescents during the coronavirus disease 2019 (COVID-19) pandemic and its restrictions. The study was conducted online during the 2020 academic year among students in three randomly selected high schools in a city center located in Eastern Turkey. The students studying in the chosen high schools who agreed to participate were included in the study ( n = 514). We found that most adolescents were anxious, had been affected in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…In nearly all age groups, the school and kindergarten closures, lack of social contacts and leisure activities associated with the pandemic were predominantly assessed negatively by parents, except in the group of 14-to under 16-year-old children, possibly because adolescents have a lower need for care and have already developed independent coping strategies like connecting with others through online platforms, including playing video games together, and social media, religious coping styles, etc. [33,34]. As there is evidence that parental practices and coping measures affect children's mental health, our study also shows that parental psychological stress had the strongest influence on child stress in every age group [12].…”
Section: Discussionsupporting
confidence: 65%
“…In nearly all age groups, the school and kindergarten closures, lack of social contacts and leisure activities associated with the pandemic were predominantly assessed negatively by parents, except in the group of 14-to under 16-year-old children, possibly because adolescents have a lower need for care and have already developed independent coping strategies like connecting with others through online platforms, including playing video games together, and social media, religious coping styles, etc. [33,34]. As there is evidence that parental practices and coping measures affect children's mental health, our study also shows that parental psychological stress had the strongest influence on child stress in every age group [12].…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, positive religious coping was associated with greater satisfaction with life and satisfaction with social support during the pandemic with fear of COVID-19 serving as a significant mediator between negative religious coping and satisfaction with life and satisfaction with social support (Dobrakowski et al, 2021). In addition, the role of negative religious coping in reducing overall well-being, satisfaction with life and quality of life has been reported in many other studies (Hebert et al, 2009;Kadiroğlu et al, 2021;Rababa et al, 2021;Scandrett & Mitchell, 2009). Moreover, research showed that religious coping styles can serve as a mediator in the association between stressors and psychological outcomes such as well-being (Helder et al, 2002).…”
Section: Religious Coping As a Mediatormentioning
confidence: 78%
“…Similar differences based on sex in the adoption of religious coping were highlighted by the research conducted in Jordan during the COVID-19 pandemic [ 59 ]. A study from Turkey highlighted the difference among adolescents as females tend to use positive religious coping while males use negative religious coping and the differences might be because of God as controlling is higher among men [ 60 ]. Study findings contradict with the previous research in India and Nigeria that identified no significant difference in adoption of religious-spiritual coping based on gender [ 61 ].…”
Section: Discussionmentioning
confidence: 99%